ANALISIS BIAYA TRANSAKSI PADA REALISASI PENERIMAAN PAJAK BUMI DAN BANGUNAN (PBB) KABUPATEN BALANGAN - Inayati Nuraini Dwiputri (LPPM Universitas Trunojoyo Madura, 2013)
Empirical studies onthe theory ofnewinstitutional economics(NIE) in particulartransaction cost analysisin the studyof taxationmainlyland and building taxcansayno. The emergence ofacceptance phenomenon of transaction costs inthe United Nations. In DistrictBalanganencourageresearchers toconductthis study. Indications ofhiddenactionas a resultofthe incompatibility ofthe UNdata objectsdefinedby the government(through the Directorate General of Taxation) withthe datain the fieldthat occursin the process ofrealization ofthe UN, indicateinefficiencies inBalanganregency governmentinstitutions, especially in the realization ofthe UNadmission. This articleusesa transactioncost analysisto determine theefficiency ofgovernmentinstitutionsBalanganregency. The purpose ofthe studyis to identifythe amount oftransaction costs involvedin maximizingrevenue realizationUNBalanganregency, identifythe type oftransaction costsaffect therealization ofthe UNacceptanceBalanganregency, analyzethe efficiency ofgovernmentinstitutionsin thedistrictBalanganminimizetransactioncostsandmaximize therealization ofthe proceedsof the UN, andidentifythe type oftransactioncoststhat most affect therealization ofthe UNacceptanceBalanganregency. Withtransactioncost analysisit is known thatinstitutionalinefficiencyinBalanganregency governmentactionandarehiddenin the realization ofthe UNacceptanceBalanganregency. From theregressionanalysisthatkind of transaction costssignificantly influence therealization ofthe UNacceptanceisthe cost of verificationanddata collection. While thecost ofthe giftandthe cost ofmonitoringandevaluationdoes not significantly influencethe realization ofthe UNadmission. There aresomepoliciesthat need to beimplementedbythe DistrictBalangantoimprove theeffectivenessandefficiency ofinstitutionalBalanganCounty Governmentin its efforts tothe realization ofthe UNadmission.